Synthesis, and evaluation of α-amylase and α-glucosidase inhibitory potential of new pyrazolo[3,4-d]pyrimidine derivatives - El-Fal, Mohammed; Sayah, Karima; Marmouzi, Ilias; Faouzi, My El Abbes; Ansar, M’hammed; Taoufik, Jamal; Essassi, El Mokhtar; Ramli, Youssef (European Journal of Chemistry, 2017)
A series of new pyrazolo[3,4-d]pyrimidine compounds were synthesized in excellent yields via sulfuration and 1,3-dipolar cycloaddition and confirmed by MS, FT-IR and NMR techniques. All the prepared compounds were screened in vitro for their α-amylase and α-glucosidase inhibitory activities. Preliminary results indicated that some target compounds exhibited promising α-amylase and α-glucosidase inhibitory activity potency. Among the tested products, the cycloadduct f was found most active inhibitor (IC50 = 134.30 μM) for α-amylase, and the sulphur product b is the most active inhibitor (IC50 = 16.37 μM) for α-glucosidase.